(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2017)
The financial fraud considers part of large concept to management and financial corruption, the financial fraud is appeared especially after corporate, that is Emerge agency theory, that is because recognize relationship between the management company and stakeholder, that is through group from constriction in order to block the management to fraud practice, that on the basis was choose another party in order fraud this practice and give opinion on financial statement, that consider basis decision making from stakeholder to basis the report auditor about creditability this is statement that reflect real activity for the company.The Auditor in order to lead work him Full professionalism to must using group from control Techniques, that is contributions to fraud detection, the Benford’s law is consider control tool and one from this Techniques that using in multiple sides in the Audit and control, and statically method provide indict to auditor about risk level in balances for accounts and transaction. The research aims to shed light the role of Auditor in risk appreciation and information control, and important Benford’s law in appreciation a fraud detection risk in financial fraud in audit.The Researchers have found gropes from conclusions its important; the Benford’s law is control tool contribution in appreciation a fraud risk actively, as well as the role it’s in the fraud detection. The researchers are grope recommendations important its should from Auditor using modern tools in audit and financial control, And the Benford’s is consider one from this technique. Keyword: Benford’s law, fraud, detection risk.